A rheumatoid arthritis patient with chronic recurrent annular neutrophilic dermatosis: Are we dealing with a new type of rheumatoid arthritis-associated dermatosis? - Ece Nur Degirmentepe; Emek Kocatürk; Tulin Yuksel; Pırıl Etikan Akbas; Ilteris Oguz Topal; Nesimi Büyükbabani (Wolters Kluwer Medknow Publications, 2017)
Neutrophilic dermatoses comprise a heterogeneous group of disorders, which are characterized by inflammatory skin lesions that share a common histopathological feature, intense inflammatory infiltration consisting primarily of neutrophils, with no evidence of vasculitis. We describe a 75-year-old man with rheumatoid arthritis, who presented with erythematous edematous plaques. The histopathological findings indicated neutrophilic dermatosis; however, the patient was afebrile and without an elevated white blood cell count or systemic involvement. We think that the most suitable expression for this variant with clinical manifestations different from those of classical Sweet syndrome is "chronic recurrent annular neutrophilic dermatosis," as introduced by Christensen et al.1